Analysis of Human Thermal Comfort in Bus Based on Thermoelectric Cooling Climate-Controlled Seats - Su, Chu-qi; Liang, Xi-xian; Wang, Yi-ping; Yang, Ya-feng; Su, Jian-jun; Liu, Xun (International journal of energy research, 2023)
In order to improve the thermal comfort of passengers, the thermoelectric cooling climate-controlled seats were set in the passenger cabin. In this study, thermoelectric cooler units’ cooling performance is studied by experiment method. The heat and flow field of the bus cabin are analyzed in four different cases (air conditioner open/closed, thermoelectric cooler open/closed) using computational fluid dynamics method. Moreover, an experiment has been conducted to verify the accuracy of the simulation method. The results show as below: the ideal working current of the thermoelectric cooler is in range of 3-4 A and the coefficient of performance value range 0.5-0.7. The climate-controlled seats can enhance the local airflow perturbation, which can increase the passengers’ overall thermal comfort by 18.96%. The thermal comfort of passengers closer to air conditioner inlet is better than passengers in other areas, and the area with the best thermal comfort for passengers are the front and rear seats of the bus cabin. As expected, the thermoelectric cooling climate-controlled seat can improve the thermal comfort of passengers, and has a broad application prospect.